Design, synthesis and biological evaluation of organotin(IV) complexes of flumequine and cetirizine - Iftikhar, Syed Hassan; Gilani, Syeda Rubina; Taj, M. Babar; Raheel, Ahmad; Ud-Din-Imtiaz, -; Termizi, Syed Ahmad; Al-Shakban, Mundher; Ali, Hapipah Mohd (Serbian Chemical Society, 2018)
Six new organotin(IV) derivatives [Me3SnL1] (1), [Bu3SnL1] (2), [Ph3SnL1] (3), [Me3SnL2] (4), [Bu3SnL2] (5) and [Ph3SnL2] (6) (where HL1 = = 9-fluoro-6,7-dihydro-5-methyl-1-oxo-1H,5H-pyrido[3,2,1-ij]quinoline-2-car-boxylic acid (flumequine) and HL2 = 2-[2-[4-[(4-chlorophenyl)phenylmethyl]--1-piperazinyl]ethoxy] acetic acid (cetirizine)) were synthesized and characterized by elemental analysis, FT-IR spectroscopy, multinuclear 1H-, 13C- and 119Sn-NMR, mass spectrometry and thermal analysis techniques. The obtained data reveal trigonal-bipyramidal geometry in case of complexes 1, 2, 4 and 5, and tetrahedral geometry for complexes 3 and 6 around the tin atom, whereas in complexes 3 and 6 the carboxylate ligand act as monodentate ligand through one of its oxygen atoms while it acts as bidentate ligand through two oxygen atoms for complexes 1, 2, 4 and 5. The antibacterial and antifungal efficacies of complexes 1–6 were assessed and the majority of the compounds showed good activities. The present research showed that the trimethyltin(IV) derivatives were particularly more effective than tributyltin(IV) and triphenyltin(IV) derivatives against all the bacterial and fungal strains. Antioxidant and DNA binding studies were also performed and promising results were obtained.